Hierarchical high-throughput SNP genotyping of the human Y chromosome using MALDI-TOF mass spectrometry. - Paracchini, S; Arredi, B; Chalk, R; Tyler-Smith, C (2002)
We have established the use of a primer extension/mass spectrometry method (the PinPoint assay) for high-throughput SNP genotyping of the human Y chromosome. 118 markers were used to define 116 haplogroups and typing was organised in a hierarchical fashion. Twenty multiplex PCR/primer extension reactions were set up and each sample could be assigned to a haplogroup with only two to five of these multiplex analyses. A single aliquot of one enzyme was found to be sufficient for both PCR and primer extension. We observed 100% accuracy in blind validation tests. The technique thus provides a reliable, cost-effective and automated method for Y genotyping, and the advantages of using a hierarchical strategy can be applied to any DNA segment lacking recombination.